Assessing conservation priorities of endemic freshwater fishes in the Tropical Andes region. Issue 7 (16th December 2018) - Tognelli, Marcelo F.; Anderson, Elizabeth P.; Jiménez‐Segura, Luz F.; Chuctaya, Junior; Chocano, Luisa; Maldonado‐Ocampo, Javier A.; Mesa‐Salazar, Lina; Mojica, José I.; Carvajal‐Vallejos, Fernando M.; Correa, Vanessa; Ortega, Hernán; Rivadeneira Romero, Juan F.; et al.
Abstract: Assessing the effectiveness of protected areas for sustaining species and identifying priority sites for their conservation is vital for decision making, particularly for freshwater fishes in South America, the global centre of freshwater fish diversity. Several conservation planning studies have used threatened freshwater fishes or species that are vulnerable to climate change as conservation targets, but none has included both in priority‐setting analysis. The objectives of this study were to identify gaps in the coverage of the existing protected areas in representing the endemic freshwater fishes of the Tropical Andes region, and to identify conservation priority areas that adequately cover threatened species and species vulnerable to climate change. Data on 648 freshwater fishes from the Tropical Andes were used to identify gaps in the protected area coverage, and to identify conservation priority sites under three scenarios: (i) prioritize threatened species; (ii) prioritize species that are vulnerable to climate change; and (iii) prioritize both threatened species and species vulnerable to climate change. A total of 571 species (88% of all species) were not covered by any protected areas; most of them are restricted to ≤10 catchments. To represent both threatened species and species vulnerable to climate change in the third scenario, 635 catchments were identified as priority areas, representing 26.5% of the study area. The number of irreplaceable catchments for this scenario is 475, corresponding to 22.5% of the total area. The results of this study could be crucial for designing strategies for the effective protection of native fish populations in the Tropical Andes, and for planning proactive climate adaptation. It is hoped that the identification of priority areas, particularly irreplaceable catchments, will help to guide conservation and management decisions in the Andean region.